2017
DOI: 10.1155/2017/6969453
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Degree Spherical Simplex‐Radial Cubature Kalman Filter

Abstract: Conventional low degree spherical simplex-radial cubature Kalman filters often generate low filtering accuracy or even diverge for handling highly nonlinear systems. The high-degree Kalman filters can improve filtering accuracy at the cost of increasing computational complexity; nevertheless their stability will be influenced by the negative weights existing in the high-dimensional systems. To efficiently improve filtering accuracy and stability, a novel mixed-degree spherical simplex-radial cubature Kalman fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Liu et al [11] proposed a interacting multiple model fifth-degree spherical simplex-radial cubature Kalman filter (IMM5thSSRCKF) by integrating the interacting multiple model (IMM) filter with the fifth-degree spherical simplex-radial cubature Kalman filter (5thSSRCKF). Wang et al [12] proposed a mixed-degree spherical simple-x-radial cubature Kalman filter (MSSRCKF), and analyzed its accuracy. Simulations results showed that the algorithm can achieve performance improvement of fifth-degree SSRCKF and has higher accuracy under less computational burden.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [11] proposed a interacting multiple model fifth-degree spherical simplex-radial cubature Kalman filter (IMM5thSSRCKF) by integrating the interacting multiple model (IMM) filter with the fifth-degree spherical simplex-radial cubature Kalman filter (5thSSRCKF). Wang et al [12] proposed a mixed-degree spherical simple-x-radial cubature Kalman filter (MSSRCKF), and analyzed its accuracy. Simulations results showed that the algorithm can achieve performance improvement of fifth-degree SSRCKF and has higher accuracy under less computational burden.…”
Section: Introductionmentioning
confidence: 99%
“…A significant observation is that a cubature rule over spherical surface that is constituted by the dth-degree spherical rule and the dth-degree radial rule can achieve a dth-degree estimation accuracy. Nevertheless, the degree of the spherical rule as shown in Algorithm 1 is not necessarily equal to the radial rule degree which facilitates and motivates the mixture-degree of cubature rules over the spherical surface [23,35].…”
Section: Efficient Cubature Rule Over the Entire N-d Spacementioning
confidence: 99%
“…The MACNCKF algorithm is commonly used in CKF and its various derivative algorithms. This section provides a discretized approximation algorithm flow based on Mixeddegree Spherical Simplex-Radial Cubature Kalman Filter (MSSRCKF) [24]. MSSRCKF is a CKF algorithm adopting mixed-order simplest phase-path sampling strategy.…”
Section: Macnckf Implementation Based On Mssrckfmentioning
confidence: 99%
“…First, there is need to calculate i ξ according to equations (24) and (25), and perform the first volume point calculation:…”
Section: Macnckf Implementation Based On Mssrckfmentioning
confidence: 99%